HUBUNGAN TINGKAT PENGETAHUAN PETANI TENTANG PERUBAHAN IKLIM DENGAN ADAPTASI BUDIDAYA STROBERI DI DESA PANCASARI, KECAMATAN SUKASADA, KABUPATEN BULELENG - Kadek Ryan Surya Negara; Made Antara; I Nyoman Dhana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
This research aims to (1) describe the strawberry farmers ‘knowledge about climate change in the village Pancasari, (2) Describe the farmer adaptation to climate change relating to the cultivation of strawberries in the village Pancasari and (3) to analyze the correlation between farmers’ knowledge about climate change and adaptation to the cultivation of strawberries in Pancasari village. This study was designed as a descriptive study, with the ecological approach. The object of research is the effect of the level of farmers’ knowledge about climate change and adaptation to the cultivation of strawberries, while the subject of the strawberry farmers in the village Pancasari. Then the data is collected using observation method, the method of recording documents and interviews, then analyzed using qualitative descriptive analysis for the formulation of the problem first and second as well as quantitative descriptive formulation of the problem for the third. The results showed (1) Knowledge strawberry farmers about climate change in high categorized Pancasari village with a score of 3.81, (2) Adaptation of farmers to climate change related to the cultivation of strawberries in the village Pancasari categorized either with a score of 4.62 and (3) There is a positive relationship level of farmers’ knowledge about adaptation to climate change to the cultivation of strawberries in the village Pancasari with r = 0.97.